East African odontopygid millipedes 1: Five new species of Xystopyge (Attems, 1909) and a proposal for a new gonopod terminology (Diplopoda; Spirostreptida; Odontopygidae) - Frederiksen, Sara B.; Enghoff, Henrik (Zootaxa, 2012)
Five new species of the endemic East African genus Xystopyge are described: X. pelecys, X. frontieri, X. proplicatus, X.biacanthus, and X. zanzibarensis. Three are from the Eastern Arc Mountains, Tanzania, two are from the UsambaraMtns. and one is from the Uluguru Mtns. One further species is from the Kenyan lowland bordering Tanzania, and onefrom the island of Zanzibar, Tanzania. Xystopyge robusta hoffmani Vandenspiegel & Pierrard, 2004, is elevated to fullspecies status: Xystopyge hoffmani n.stat. A new gonopod terminology for Odontopygidae, adapted from Hoffman’s(2008) terminology for the related family Spirostreptidae, is used for the descriptions of the new species. New records of previsously described Xystopyge species are given.